Pengaruh Youtuber Gadget Review, Desain, Customer Trust dan Kelengkapan Fitur Terhadap Minat Beli Smartphone Samsung - Damayanti, Erika; Rizal, Mohammad; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of YouTuber gadget reviews, design, customer trust and completeness of features on Samsung smartphone buying interest